Representation of jihadis in european media ( critical discourse analysis on terrorism issue in the guardian news report posted on April 13 th 2017 ) - Artha Nur Restia Panji (Fak. Adab dan Ilmu Budaya UIN Sunan Kalijaga, 2021)
et,1/irh,c.1